Cold tolerance strategy and cryoprotectants of Megabruchidius dorsalis in different temperature and time stresses - Chen, Si-Yu; Zhao, Ru-Na; Li, You; Li, He-Ping; Xie, Ming-Hui; Liu, Jian-Feng; Yang, Mao-Fa; Wu, Cheng-Xu (Frontiers in Physiology, 2023)
The honey locusts (genus Gleditsia) are a genus of high-value trees in Asia. Seed beetle, Megabruchidius dorsalis (Fåhraeus) (Col.: Chrysomelidae: Bruchinae), is a Gleditsia oligophagous pest that causes severe yield reduction. To understand the cold tolerance of M. dorsalis adults, this study investigated its cold tolerance strategy and the influence of low temperatures on its physiology and biochemistry. The low-temperature treatments were divided into three groups: long-term temperature acclimation (Group 1; 15 °C, or 20 °C, or 25 °C, or 28 °C [control check, CK] for 10 days), short-term low-temperature exposure (Group 2; 0 °C or 4 °C for 2 h), and long-term low-temperature induction (Group 3; 0 °C or 4 °C for 1 d, 3 d, or 5 d). The supercooling point (SCP; temperature at which spontaneous nucleation and ice lattice growth begin), freezing point (FP; temperature at which insect fluids freeze), low lethal temperature (LLT; temperature at which all individuals are killed), water, lipid, glycerol, and total sugars contents were measured under different temperature stresses. The results showed that M. dorsalis adults were a freeze-avoidant species. The SCP and LLT at 28 °C were -10.62 °C and -19.48 °C, respectively. The SCP and FP of long-term temperature acclimation (15 °C, or 20 °C, or 25 °C) were significantly lower than that of the control group (28 °C). The water content of the long-term low temperature induction (0 ℃) group was significantly lower than that of the control group. The lipid and glycerol content in the acclimated group at 20 °C and 25 °C were significantly higher than in the control group. M. dorsalis adults may maintain their biofluids in a supercooled state via cryoprotectant accumulation and cryoprotective dehydration to prevent ice nucleation. This study provides a theoretical basis for future research on overwintering and potential distribution and related prediction of M. dorsalis adults.